2021
DOI: 10.1097/scs.0000000000008204
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Endonasal Endoscopic Skull Base Repair in Posttraumatic Tension Pneumocephalus

Abstract: Objectives: Information about the endonasal endoscopic approach (EEA) for the management of posttraumatic tension pneumocephalus (PTTP) remains scarce. Concomitant rhinoliquorrhea and posttraumatic hydrocephalus (PTH) can complicate the clinical course. Methods: The authors systematically reviewed pertinent articles published between 1961 and December 2020 and identified 6 patients with PTTP treated by EEA in 5 reports. Additionally, the authors share their institutional experience including a seventh patient,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Recent studies have explored various endoscopic techniques that simultaneously address the resolution of traumatic tension pneumocephalus (TP) and the closure of the bone defect responsible for cerebrospinal fluid leakage in a single surgical stage (6,7). The development of new techniques and more angulated instruments for endoscopic surgery has increased the possibility of accessing more challenging endonasal areas (8).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have explored various endoscopic techniques that simultaneously address the resolution of traumatic tension pneumocephalus (TP) and the closure of the bone defect responsible for cerebrospinal fluid leakage in a single surgical stage (6,7). The development of new techniques and more angulated instruments for endoscopic surgery has increased the possibility of accessing more challenging endonasal areas (8).…”
Section: Discussionmentioning
confidence: 99%
“…[18,19] PN is commonly associated with various events such as post-craniotomy or surgical interventions, barotrauma, ear infections, exposure to nitrous oxide or induced nitrogen anesthesia, and diagnostic procedures (e.g., lumbar puncture). [20,21] While the location of PN may vary, it typically manifests with the presence of air in the apical space and encompasses intraventricular, intraparenchymal, subarachnoid, subdural, and epidural areas.…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant advances in understanding the pathophysiology of PN, the documentation remains limited, with only six confirmed cases of PN and only four cases of TPN properly documented regarding patients with NPC. [19][20][21] Several mechanisms have been identified to explain the occurrence of TPN, with barotrauma being one of the most studied. In this regard, Kankane et al (2016) reported the case of a 50-year-old man who developed TPN due to high air pressure (hyperbaric) following epidural steroid injections for the treatment of cervical radiculopathy.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent literature review, Dalolio et al described the endoscopic endonasal approach as an effective second-line treatment of symptomatic posttraumatic TP [ 15 ]. Li et al [ 9 ] reported 26 cases of TP caused by endoscopic endonasal surgery collected in an English literature review: 11 cases were caused by an ethmoidal defect, and the therapeutic approach was based on a defect multilayer closure with or without craniotomy.…”
Section: Discussionmentioning
confidence: 99%